2008
DOI: 10.1007/s11661-008-9622-2
|View full text |Cite
|
Sign up to set email alerts
|

Tetragonality and Properties of Ba(Zr x Ti1−x )O3 Ceramics Determined Using the Rietveld Method

Abstract: Ti 12x )O 3 (x = 0, 0.05, 0.1, and 0.15, BZT for short) has been prepared using the solid solution reaction from BaTiO 3 (BT) and BaZrO 3 (BZ). For transmission electron microscopy (TEM) analysis, the cubic phase of BZT coexists with the tetragonal one in the Ba(Zr 0.15 Ti 0.85 )O 3 ceramics. Its structure of ceramics has been estimated using the Rietveld and Cohen methods. The effect of BaZrO 3 content on the tetragonality of BZT and its relation to a dielectric constant have been studied, and it is found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…There are two theories reported in the literatures which can be used to explain the sintering procedure related DPT behavior in BZT ceramics. Firstly, the coexistence of ferroelectric and paraelectric phases in the structure of BZT20 ceramics near room temperature gives rise to DPT behavior, which can be attributed to the distribution of mechanical stress in the material or variation in chemical composition caused by the sintering process [23,24]. Secondly, freezing degree of paraelectric clusters to the ferroelectric phase influences the grade of DPT [25] which is found to be increased with increasing sintering temperature in BZT20 ceramics.…”
Section: Resultsmentioning
confidence: 98%
“…There are two theories reported in the literatures which can be used to explain the sintering procedure related DPT behavior in BZT ceramics. Firstly, the coexistence of ferroelectric and paraelectric phases in the structure of BZT20 ceramics near room temperature gives rise to DPT behavior, which can be attributed to the distribution of mechanical stress in the material or variation in chemical composition caused by the sintering process [23,24]. Secondly, freezing degree of paraelectric clusters to the ferroelectric phase influences the grade of DPT [25] which is found to be increased with increasing sintering temperature in BZT20 ceramics.…”
Section: Resultsmentioning
confidence: 98%
“…These patterns reveal a perovskite-type tetragonal structure, which is in harmony with existing literature ref. 15 , 27 and 28 . The concentric halo rings observed in the electron diffraction patterns distinctly indicate the nanocrystalline nature of the material, with bright spots within these rings signifying high crystallinity.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed for all compositions the formation of a phase compound isostructural with the cubic (Pm-3m) BaTiO 3 . Hong-Hsin Huang [19] have studied the tetragonality of Ba(Zr x Ti 1-x )O 3 ceramics using the Rietveld Method and they observed that both lattice parameters a and c continuously approach each other when the Zr 4+ is increased. This phenomenon is caused by Ti 4+ replacing Zr 4+ at the B site of the perovskite structure, creating an enlargement of the B site and thus a larger increase of the a value than the c value.…”
Section: Resultsmentioning
confidence: 99%